2011
DOI: 10.4103/0253-7613.81510
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Rosa canina L. leaf extract as an antidiarrheal drug in rodents

Abstract: Objectives:The objective of the study was to investigate the effect of the leaf extract of Rosa canina L. against experimental diarrhea induced by castor oil in rodents.Materials and Methods:The methanol extract of Rosa canina L. (30 and 60 mg/kg body weight) was administered orally to two groups of mice (five animals per group) in order to evaluate the activity of the extract against the castor oil-induced diarrhea model in mice. Two other groups received normal saline and diphenoxylate (5 mg/kg) as positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…27 Different authors also reported total phenolic content, total flavonoid content, as well as total flavonol aglycone levels in the leaf extracts of various Rosa species. 27 Different authors also reported total phenolic content, total flavonoid content, as well as total flavonol aglycone levels in the leaf extracts of various Rosa species.…”
Section: Chemical Analysismentioning
confidence: 99%
“…27 Different authors also reported total phenolic content, total flavonoid content, as well as total flavonol aglycone levels in the leaf extracts of various Rosa species. 27 Different authors also reported total phenolic content, total flavonoid content, as well as total flavonol aglycone levels in the leaf extracts of various Rosa species.…”
Section: Chemical Analysismentioning
confidence: 99%
“…This hypothesis is in agreement with that previously suggested by many researchers for different plant extracts exerting antidiarrheal activity. [ 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Rosa canina L. possesses therapeutic activities against various inflammatory disorders such as rheumatism, arthritis and gout, in addition to other diseases like cold and influenza [ 19 , 20 ]. Rosa canina L. was used as a treatment for gastrointestinal tract diseases such as gastric ulcers [ 21 ] and diarrhea [ 22 ]. The biological activities of Rosa canina L. are attributed to the high levels of bioactive molecules such as vitamin C, carotenoids, anthocyanins, and phenolic acids [ 16 , 23 ].…”
Section: Introductionmentioning
confidence: 99%